(untitled) (Zien Journal of Social Sciences and Humanities, 2022)
This article talks about the views of the great writer Abdulla Avloni, who has taken education and training as the main idea in his works, the honorable representative of our nation, who is calling on the youth to be literate and enlightened through his works